Real time online multiplayer gaming framework using kinect sensors - Ahmed, Imtiaz; Shabab, Khondokar Sadman; Hossain, MD. Shahadat; Akand, MD.Tashauf; Majumder, Shovon (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.